“RATIFIKASI PIAGAM ASEAN BERDASARKAN KEDAULATAN HUKUM INDONESIA” - Fachruddin Razi (Universitas Batanghari Jambi, 2014)
This paper discuss about whether the ratification of the ASEAN Charter in accordance with Indonesian sovereignty. Results of this study indicate that a treaty is apply before it was officially implemented in Indonesia. This is because UU (the Act) of Ratification is interpreted as approval's DPR (House of Representative) that given to President to ratify a treaty or a charter. That's why, ASEAN Charter applies first before it was enacted in Indonesia. Result of this construction is illogical, how can be possible, Indonesia is bound to a treaty or a charter which hasn't applied yet. Although Indonesia has been engaged in a treaty, but as a sovereign country, Indonesia still has the right to independently (unilateral) to withdraw from the treaty if it is detrimental to the sovereignty of the Indonesia state. Therefore, as the State supremacy of the constitution, a new foundation need to be formalized in UUD 1945 (the Constitution of the Republic of Indonesia of 1945) by amending Article 11 of the UUD 1945.Keywords: Ratification, Treaty, ASEAN Charter, Article 11 UUD 1945